An Empirical Study on Bank Profitability Determinants: Evidence from US - Kabir, Sara Bintey (2022)
The emphasis placed by scholars on determining the way to a more efficient and profitable banking industry has inspired this research. This study examines the determinants of bank profitability from the year of 2001 to 2020 using an unbalanced panel dataset of 434 US commercial banks with 5248 observations. The System Generalized Method of Moments (SGMM) is utilized to analyse the key bank-specific, industry-specific, and macroeconomic determinants of profitability in US commercial banks. As an important component of bank-specific variables cost-efficiency of bank is calculated using the Battese and Coelli (1995) stochastic frontier model. The computed average cost efficiency score of banks during the last 20 years is 85.9%, according to the results. The scores have an overall upward trend with two major downturns during global financial crisis and Covid-19. The profitability determinants analysis exhibits that profitability is significantly influenced by eight different variables. The profitability of US commercial banks is positively associated with previous year’s profit, cost-efficiency, GDP growth rate, inflation and unemployment rate. However, it is inversely correlated with bank size, liquidity and credit risk.